Listening to Noise: An Interactive Soundscape Installation that Transforms Place in the Service of Intangible Cultural Heritage - Liu-Rosenbaum, Aaron (Material Culture Review, 2016)
Emerging technologies offer unprecedented opportunities for creating and preserving intangible cultural heritage. At the same time, these technologies pose fresh challenges to both our understanding and preservation of cultural heritage as new practices emerge through the interchange between traditional practices and current technologies. In the field of music, these new practices have blurred an already tenuous distinction between music and noise, which requires a more inclusive definition of intangible cultural heritage with regard to sound. This article will examine the case of an interactive sound installation that engaged the local community with environmental noise in the form of a sound portrait of Quebec as a lens through which to explore the above issues.